2015
DOI: 10.1128/iai.01184-15
|View full text |Cite
|
Sign up to set email alerts
|

CD8 + T Cell Exhaustion, Suppressed Gamma Interferon Production, and Delayed Memory Response Induced by Chronic Brucella melitensis Infection

Abstract: dBrucella melitensis is a well-adapted zoonotic pathogen considered a scourge of mankind since recorded history. In some cases, initial infection leads to chronic and reactivating brucellosis, incurring significant morbidity and economic loss. The mechanism by which B. melitensis subverts adaptive immunological memory is poorly understood. Previous work has shown that Brucellaspecific CD8؉ T cells express gamma interferon (IFN-␥) and can transition to long-lived memory cells but are not polyfunctional. In this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
40
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(41 citation statements)
references
References 58 publications
1
40
0
Order By: Relevance
“…Although the numbers of cytokine-producing CD4 + T cells exceeded CD8 + T cells in znBAZ-vaccinated mice, about one-third of the total IFN-γproducing TCRβ + cells were CD8 + T cells. It has been presumed that CD4 + T cells are the major source for IFN-γ and TNF-α [42,43], and only a handful of studies has implicated the importance of CD8 + T cells [40,44]. The route of vaccination may be a contributing factor in CD8 T cell elevations [19, 45, 46].…”
Section: Discussionmentioning
confidence: 99%
“…Although the numbers of cytokine-producing CD4 + T cells exceeded CD8 + T cells in znBAZ-vaccinated mice, about one-third of the total IFN-γproducing TCRβ + cells were CD8 + T cells. It has been presumed that CD4 + T cells are the major source for IFN-γ and TNF-α [42,43], and only a handful of studies has implicated the importance of CD8 + T cells [40,44]. The route of vaccination may be a contributing factor in CD8 T cell elevations [19, 45, 46].…”
Section: Discussionmentioning
confidence: 99%
“…Durward-Diioila et al showed that chronic infection of mice with B . melitensis led to CD8+ T cell exhaustion, manifested by programmed cell death 1 (PD-1) and lymphocyte activation gene 3 (LAG-3) expression and a lack of IFN-γ production [39]. This is indicative of the importance of cytotoxic CD8+ T cells in a protective immune response against Brucella infections.…”
Section: Discussionmentioning
confidence: 99%
“…One possible explanation for this early clearance are natural killer cells, which have been recently shown to mediate clearance of Y. pseudotuberculosis in the mesenteric lymph nodes (Rosenheinrich et al, 2015). Beyond early clearance, the possibility exists that Yersinia could escape CD8+ T cell recognition by down-regulating antigen expression to avoid antigen-specific T cell recognition, or inducing T cell exhaustion (Durward-Diioia et al, 2015). The latter is due to the semi-chronic nature of Yersinia infection in the Lm- OVA-immune mice.…”
Section: Discussionmentioning
confidence: 99%